Penyuluhan Kesehatan Dan Keselamatan Bagi Para Ibu Rumah Tangga Di Desa Naga Umbang Kecamatan Lhoknga Aceh - Bachtiar, Dandi; Razali; Sabri; Masri; Ali, Nurdin; Zulfan (Yayasan Kawanad, 2023)
Building a safety culture in the home or family environment will tend to be more difficult than building a safety culture in the workplace. This community service program aims to provide health and safety education to housewives in Naga Umbang Village, Lhoknga District, Aceh. Through various outreach activities, such as seminars, workshops and practical demonstrations, it is hoped that housewives can increase understanding and awareness of the importance of good health practices and safety measures in everyday life. It is hoped that the results of this program evaluation can provide constructive input for continuous improvement and increasing the welfare of local communities.